2004
DOI: 10.1152/ajpheart.00878.2003
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic preconditioning exaggerates cardiac damage in PKC-δ null mice

Abstract: Ischemic preconditioning confers cardiac protection during subsequent ischemia-reperfusion, in which protein kinase C (PKC) is believed to play an essential role, but controversial data exist concerning the PKC-delta isoform. In an accompanying study (26), we described metabolic changes in PKC-delta knockout mice. We now wanted to explore their effect on early preconditioning. Both PKC-delta(-/-) and PKC-delta(+/+) mice underwent three cycles of 5-min left descending artery occlusion/5-min reperfusion, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 52 publications
4
71
1
2
Order By: Relevance
“…We have previously demonstrated in an in vivo mouse model of myocardial infarction, that PKC␦ deficiency (PKC␦ Ϫ/Ϫ ) is associated with a reduction of infarct size. 2 Consistent with the findings described in the DELTA MI trial, this difference failed to reach statistical significance. However, we also observed that ischemic preconditioning before index ischemia resulted in exaggerated myocardial injury in PKC␦ Ϫ/Ϫ hearts as shown by biomarker measurements (creatine kinase MB, troponin T, and lactate dehydrogenase isoenzyme 1) and triphenyltetrazolium chloride delineation of infarction.…”
Section: To the Editorsupporting
confidence: 74%
“…We have previously demonstrated in an in vivo mouse model of myocardial infarction, that PKC␦ deficiency (PKC␦ Ϫ/Ϫ ) is associated with a reduction of infarct size. 2 Consistent with the findings described in the DELTA MI trial, this difference failed to reach statistical significance. However, we also observed that ischemic preconditioning before index ischemia resulted in exaggerated myocardial injury in PKC␦ Ϫ/Ϫ hearts as shown by biomarker measurements (creatine kinase MB, troponin T, and lactate dehydrogenase isoenzyme 1) and triphenyltetrazolium chloride delineation of infarction.…”
Section: To the Editorsupporting
confidence: 74%
“…184 PKCε is also translocated to the sarcoplasmic reticulum where it reduces calcium content. 185 The role of the PKCδ isoform in IPC is more controversial, and both protection 186 and injury 187 through PKCδ activation were reported. This controversy continued into a recent clinical trial, in which-after promising preliminary datathe PKCδ inhibitor delcasertib, when given before reperfusion, failed to protect patients with reperfused AMI in terms of IS reduction, as reflected by creatine kinase-muscle band release.…”
Section: Protein Kinase Cmentioning
confidence: 99%
“…Instead, the phenotypes have been endocrine, immunological, and neural (reviewed in ref. 58), and only under physiological stress such as ischemia-reperfusion or pressure overload have subtle cardiac phenotypes been provoked (54,59,60). Does the absence of a cardiac phenotype associated with PKC isoform gene ablation indicate that the postulated roles for these kinases, based upon their activation in heart disease and their effects on hypertrophy of cultured cardiomyocytes, were incorrect?…”
Section: Gq/11 and Their Effectorsmentioning
confidence: 99%
“…Although it has long been recognized as being activated in myocardial ischemia, relatively little is known about this PKC isoform in cardiac hypertrophy. A cardiac PKCδ-transgenic mouse model has not been described, and PKCδ-knockout mice have no basal cardiac phenotype (56,60). Translocation modification has confirmed that PKCδ is a critical mediator of postischemic cardiomyocyte necrosis and contractile dysfunction in mice, rats, and pigs (71,72).…”
Section: Effects Of Pkc Isoforms On Cardiac Hypertrophy and Contractimentioning
confidence: 99%